On Acanthogonyaulax spinifera (Dinophyceae). Issue 5 (2nd September 2020) - Carbonell-Moore, Consuelo; Mertens, Kenneth Neil
ABSTRACT: The genus Acanthogonyaulax (Kofoid) H.W.Graham is a rarely observed tropical gonyaulacoid dinoflagellate, first documented at the end of the 19th century. It was initially described as a species of Ceratocorys F.Stein, then transferred to Gonyaulax Diesing, and finally to its own genus, Acanthogonyaulax . Discrepancies in the observations of its plate pattern were responsible for these changes. In this study, material from the Pacific and Indian Oceans provided evidence that Acanthogonyaulax, in spite of its similarities in plate pattern to Gonyaulax, has sufficiently important morphological differences to merit being its own genus.